THE USE OF DIENES BLOCK TOOLS TO INCREASE ACTIVITIES OF STUDENT LEARNING OUTCOMES IN MATHEMATICS LEARNING OPERATING MATERIALS CALCULATING DISABILITY - Ina Karlina; Juju Parlina; Anugrah Ramadhan Firdaus (COLLASE (Creative of Learning Students Elementary Education), 2018)
Based on the results of preliminary observations made on learning the operating material count number, it was seen that the use of instructional media was less precise, so that students' activities and learning outcomes were not optimal, whereas, student learning activities and results that involved active roles of students could provide a more meaningful learning experience. Based on these problems, the purpose of this study was to improve students' mathematics learning outcomes in the addition of chopped numbers through the use of dienes teaching aids in class 2 SDN 226 Arcamanik Endah Kec. Arcamanik. The research model used by researchers is based on Kurt Lewin's model in each cycle there are four stages, namely planning, implementing (action), observation and reflection. The method used is descriptive method. This means that after getting the data needed, the author analyzes the data by describing the findings of the data, discusses and draws conclusions. From the analysis of this study it can be seen that the students' mathematics learning outcomes in the sum of the number without the use of teaching aids obtain an average value 67.30 increased in cycle 1 after using dienes block props to be 77, 57 and after undergoing improvement in cycle 2 it increased again to 78.65.